Inducing LTD-Like Effect in the Human Motor Cortex with Low Frequency and Very Short Duration Paired Associative Stimulation: An Exploratory Study. (19th January 2016) - Srivanitchapoom, Prachaya; Park, Jung E.; Thirugnanasambandam, Nivethida; Panyakaew, Pattamon; Ramos, Vesper Fe Marie; Pandey, Sanjay; Wu, Tianxia; Hallett, Mark
Abstract : Introduction. Paired associative stimulation (PAS) is an established technique to investigate synaptic plasticity in the human motor cortex (M1). Classically, to induce long-term depression- (LTD-) or long-term potentiation-like effects in the human M1, studies have used low frequency and long duration trains of PAS. In the present study, we explored an LTD-like effect using very short duration and low frequency of P A S 10 m s protocols in human M1. Methods. Six protocols of low frequency P A S 10 m s (ranging from 0.2 Hz to 1 Hz) were investigated with very short durations of 1 and 2 minutes stimulation. Six healthy volunteers were included in each protocol. We obtained motor-evoked potentials from right abductor pollicis brevis muscle before and after applying P A S 10 m s up to 30 minutes. After we found P A S 10 m s protocol which induced an LTD-like effect, we tested that protocol on additional 5 subjects. Results. One-way repeated-measures ANOVA showed that only the group of 1-minute stimulation of 0.25 Hz induced an LTD-like effect. When adding the additional subjects, the effect remained and lasted for 30 minutes. Conclusion. Low frequency and very short duration of P A S 10 m s potentially induced an LTD-like effect in human M1. With further verification, this method might be useful for research relating to synaptic plasticity by reducing the duration of study and minimizing subject discomfort.